Encyclopedia of technology and innovation management - Narayanan, V. K. (Veekay); O'Connor, Gina Colarelli (Wiley, 2010)
This volume focuses on the relatively young field of technology and innovation management, which is of growing interest to academics, students and practitioners as they engage more in questions surrounding the origin of innovation and the impact of changing technologies